Y-chromosome diversity in Native Mexicans reveals continental transition of genetic structure in the Americas - Sandoval-Mendoza, Karla; Mendizabal, Isabel; López Valenzuela, María; Peñaloza-Espinosa, Rosenda; López-López, Marisol; Calafell, Francesc; Comas, David (American Journal of Physical Anthropology, 2012)
Sandoval, Karla et al. The genetic characterization of Native Mexicans is important to understand multiethnic based features influencing the medical genetics of present Mexican populations, as well as to the reconstruct the peopling of the Americas. We describe the Y-chromosome genetic diversity of 197 Native Mexicans from 11 populations and 1,044 individuals from 44 Native American populations after combining with publicly available data. We found extensive heterogeneity among Native Mexican populations and ample segregation of Q-M242* (46%) and Q-M3 (54%) haplogroups within Mexico. The northernmost sampled populations falling outside Mesoamerica (Pima and Tarahumara) showed a clear differentiation with respect to the other populations, which is in agreement with previous results from mtDNA lineages. However, our results point toward a complex genetic makeup of Native Mexicans whose maternal and paternal lineages reveal different narratives of their population history, with sex-biased continental contributions and different admixture proportions. At a continental scale, we found that Arctic populations and the northernmost groups from North America cluster together, but we did not find a clear differentiation within Mesoamerica and the rest of the continent, which coupled with the fact that the majority of individuals from Central and South American samples are restricted to the Q-M3 branch, supports the notion that most Native Americans from Mesoamerica southwards are descendants from a single wave of migration. This observation is compatible with the idea that present day Mexico might have constituted an area of transition in the diversification of paternal lineages during the colonization of the Americas. Copyright © 2012 Wiley Periodicals, Inc. Peer Reviewed